1998
DOI: 10.1074/jbc.273.19.11521
|View full text |Cite
|
Sign up to set email alerts
|

Human Protein S Cleavage and Inactivation by Coagulation Factor Xa

Abstract: Human factor Xa specifically cleaves the anticoagulant protein S within the thrombin-sensitive domain. Amino-terminal amino acid sequencing of the heavy chain cleavage product indicates cleavage of protein S by factor Xa at Arg 60 , a site that is distinct from those utilized by ␣-thrombin. Cleavage by factor Xa is unaffected by the presence of hirudin and is completely blocked by tick-anticoagulant-peptide and D-Glu-GlyArg-chloromethyl ketone, the latter two being specific inhibitors of factor Xa. The cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
36
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 47 publications
8
36
0
Order By: Relevance
“…These recent findings are in accordance with our observations here that protein S binds to fXa but not to fVIIa. It is likely that protein S-fXa interactions play a part in these functions of protein S. Our results are also compatible with observations of Long et al (7), who showed that fXa cleaves protein S at Arg 60 of the TSR and that this reaction requires negatively charged phospholipids and calcium ions.…”
Section: Discussionsupporting
confidence: 82%
“…These recent findings are in accordance with our observations here that protein S binds to fXa but not to fVIIa. It is likely that protein S-fXa interactions play a part in these functions of protein S. Our results are also compatible with observations of Long et al (7), who showed that fXa cleaves protein S at Arg 60 of the TSR and that this reaction requires negatively charged phospholipids and calcium ions.…”
Section: Discussionsupporting
confidence: 82%
“…Surprisingly, we found a positive correlation between cleaved PS concentrations and APC cofactor activity (r ϭ 0.51). Indeed, cleaved PS was devoid of APC cofactor activity in a FVIII proteolysis assay (12 ) and in a global coagulation test (13 ), and the lack of such activity was confirmed in this assay. This correlation could reflect a shift in total and free PS.…”
Section: Discussionmentioning
confidence: 99%
“…PS also contains a protease-sensitive loop, called the thrombin-sensitive region, between the ␥-carboxyglutamic acid-containing domain and the first epidermal growth factor-like domain. Under physiologic conditions, the thrombin-sensitive region can be cleaved after Arg 60 (11 ), and this cleavage can be reproduced in vitro by factor Xa (FXa) (12 ). The resulting two-chain disulfidelinked protein can no longer potentiate APC activity (13 ).…”
mentioning
confidence: 99%
“…The Gla domain of Ci-Gla4 is separated from the first EGF domain by a short putative disulfide loop that occupies a position analogous to the proteolytically sensitive loop of Protein S (27,28), as well as to a disulfide loop in Gas6 that is not known to be cleaved by proteases. The common evolutionary origin of Ci-Gla4, Protein S, and Gas6 is further suggested by the observation that this disulfide loop is encoded by a single exon for all three proteins.…”
Section: Full-length Sequences Of C Intestinalis Gla Domain Proteinsmentioning
confidence: 99%